Nitrogen availability effects on gas exchange measurements in field-grown maize (Zea mays L.) under irrigated Mediterranean conditions - Isla, Ramón; Guillén, Mónica; Salmerón, Montserrat (Spanish Journal of Agricultural Research, 2016)
There are limited studies about the effect of nitrogen (N) deficiency on leaf growth, N status, and photosynthetic capacity of maize grown under field conditions in a Mediterranean climate. The objective of this work was to evaluate the effect of different levels of mineral N availability on leaf gas exchange parameters of sprinkler irrigated maize. The experiment was conducted in a conventional maize field located in the central part of the Ebro valley (Spain) during two seasons. Using a portable LICOR-6400 equipment, instantaneous measurements and light response curves to gas exchange were conducted in plots with different levels of N supply ranging from deficient (no fertilized) to over-fertilized (300 kg N/ha). In addition to gas exchange measurements, mineral soil N content, chlorophyll meter readings (CMR), leaf N content, and grain yield were measured in the different plots. Results showed that grain yield reached a plateau (14.5 Mg/ha) when the mineral N available was about 179 kg/ha. CMR were linearly and highly related to total N in ear leaves. The relationship between light-saturated leaf photosynthesis measurements and CMR was significant but very weak (R2=0.13) at V8 and V14 stages but increased later in the growing season (R2=0.52). Plants with intermediate levels of N supply (48<CMR<54) tended to have slightly higher assimilation rates than plants with higher CMR readings. As the available N increased, the saturation point, the light compensation point and significant increases of dark respiration rate were observed. Under the conditions of the study, leaf N contents of 1.9% in the ear leaf were enough to maximize leaf assimilation rates with no need to over-fertilize the maize crop.